The Saraxbari Buzruk Maqam And The Analysis Of Its First Melodic Piece - Afruza Yunusaliyeva (Periodica Journal, 2025)
This article analyzes the first tarona of the Saraxbory Buzruk maqom from a musical-theoretical perspective. It explores the modal-tonal structure, melodic organization, rhythmic characteristics, and performance style of the piece. The study highlights the stages of melodic development and the artistic significance of this tarona within the maqom tradition. The analysis concludes that the first melodic piece of Saraxbory Buzruk exemplifies artistic harmony, emotional depth, and the refined aesthetics of Uzbek classical music
Keywords: maqom; Saraxbory Buzruk; tarona; mode